Assessing stakeholder participation in coastal zone management: Methodological proposal and its application in a case study from Cádiz Bay, Andalusia (Spain) - Cioffi, Giovana [UNESP]; Sanabria, Javier Garcia; Sansolo, Davis Gruber [UNESP]; Pegorelli, Camila; de Andrés, Maria (Elsevier, 2024)
Stakeholder participation (SP) is widely acknowledged in the literature as a vital tool for improving coastal zone management (CZM) and facilitating conflict mediation, resource allocation, and program implementation. However, in Spain, as in other countries, participation in CZM faces significant challenges, including underrepresentation, limited stakeholder influence in decision-making, and various resource-related issues. Despite the robust theoretical framework established in the literature, practical methods for evaluating SP and overcoming these challenges are lacking, with most efforts focused on assessing processes rather than outcomes. This study addresses this gap by proposing a systematic assessment approach built on criteria and operational indicators capable of assessing stakeholder participation in CZM from the process to its outcomes. It also examines stakeholder participation in PAs and CZs of Cádiz Bay (Spain) through the application of this approach to identify which of these challenges are present in the region, highlighting areas for improvement. The approach was developed through a multistep process, including identifying participation components via a literature review, categorizing these components into each participation dimension (who, when, how, why), formulating criteria and indicators based on these components, consulting and validating with experts, and operationalizing the approach through an analysis matrix. Data collection involved reviewing official documents, minutes of participatory arenas, and stakeholder interviews. The approach comprises six criteria - representativeness, timing, promotion, accountability and clearness, influence, and effectiveness - providing a valuable tool for understanding the progression and outcomes of participatory processes. However, the findings also highlight the need for refinement to better capture the quality and significance of participation and to make it more applicable beyond scientific research contexts. The application of the approach in Cádiz Bay revealed challenges such as underrepresentation, limited influence, resource constraints, transparency issues, and effectiveness in fostering cooperation and trust. Participation also appears to be sectorized, reflecting the fragmented institutional framework in the CZM of Cádiz Bay.
Keywords: Coastal zone management; Evaluation method; Participation; Protected areas